RELEVANSI NILAI-NILAI PENDIDIKAN KARAKTER DALAM AL-QUR’AN PADA PENDIDIKAN DI INDONESIA - Irsyadul Hakim; Agus Akhmadi; Rido Kurnianto (TARBAWI:Journal on Islamic Education, 2019)
Islamic education is an educational process that originates from the Qur'an and as-Sunnah. Al-Qur'an has included various character values in the stories of prophets and apostles. This study aims to describe the character values contained in the Qur'an. These values have relevance to the values of character education in Indonesia. This study uses a research library research approach by examining the values of character education in the Koran. The references used are books relating to the interpretation of the Koran and text-based character education books. The results found are 1) there are 17 character values in the Qur'an. (2) these values are relevant to the character values that have been set by national education because of the similarity of meaning and purpose, namely students have character as civilized individuals in all aspects of life. This research is a paper that makes the Qur'an as the main object of discussion. Therefore the results of this study can be used by Muslims as a reference in various educational institutions and propaganda.